Selective role of Mediator tail module in the transcription of highly regulated genes in yeast - Ansari, Suraiya A. (Landes Bioscience, 2012)
The tail module subunits of Mediator complex are targets of activators both in yeast and metazoans. Here we discuss recent evidence from studies in yeast for tail module specificity for SAGA-dependent, TATA-containing genes including highly regulated stress response genes, and for independent recruitment and function of the tail module.